Experimental investigation of a diesel engine operated with oxygenated linseed oil. (2021) - Daniel, Freedon; Muthu, Kannan; Balamurugan, Dhanusiya; Adhithan, Balamurugan; Govindaraj, Elavarasan
Abstract: The increase in use of biodiesel because of its exceptional properties makes it essential to study in depth about the consequences of combustion of biodiesel in diesel engine and the pollutant gases. There are numerous methods to make biodiesel but we chose to use linseed as it is easily available and its cultivation is widely done in India. In this study cold pressed linseed oil was used to produce linseed biodiesel by using transesterification method. The linseed biodiesel once generated was blended along with petroleum diesel to obtain LS5 (5% Linseed Biodiesel, 95% diesel), LS10 (10% Linseed Biodiesel, 90% diesel) and LS15 (15% Linseed Biodiesel, 85% diesel). These ratios of mixtures will be used as samples to do the performance and emission tests of this Biodiesel to analyze the properties of the Biodiesel and compare them with pure diesel data obtained when used as fuel in a 3.5 kW 4 S single cylinder diesel engine. Also we have used nano-additives to see how it alters the biodiesel properties and makes it more suitable as a fuel in terms of emissions and its performance.